What do students prefer - Use Cases, User Story or DT Techniques? - Duarte, José Carlos; Damian, Adriana Lopes; Conte, Tayana (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2022)
Teaching software requirements specifications can be challenging since students must learn the notations and representation of the problem domain in different software development contexts. So, one of the factors that impact the quality of requirements specifications can be the type of training received by software engineers. Given this context, In this paper, we present an exploratory study about the application of three different approaches for requirements specifications: in a traditional software context, applying UML Use Cases; in an agile context with User Stories; and a new technique proposed in Design Thinking (DT) context. We analyzed undergraduate students’ perceptions about the application of each one, including the ease, difficulty, usefulness, and adoption in future projects. The results present the participants’ perceptions about the techniques, and point out that the User Story is the easiest, and the most limited and most appropriate for the initial phases of a software process. The Use Case and the UJB shared a good part of the difficulties and facilities. But, the latter offers a wider range in relation to its use. The article shows SE teachers the benefits that each approach can offer not only for the specification of requirements, but for the entire software development process. Our research benefits instructors interested in understanding the students’ perceptions about software requirements specifications in such contexts, contributing to software quality teaching of them.